Ethics and social responsibility: Asian and western perspective - Chan, Gary; Shenoy. George TL (Singapore, 2009)
The book is an understanding of theory to appreciate and reflect on the logical and persuasiveness of a particular ethical stance.
Keywords: Professional Ethics; Social Ethics